2018
DOI: 10.3390/rs10060882
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TRMM/GPM Blended Daily Products over Brazil

Abstract: The precipitation estimates from the Tropical Rainfall Measuring Mission (TRMM) Multi-satellite Precipitation Analysis (named TMPA and TMPA-RT for the near real-time version) are widely used both in research and in operational forecasting. However, they will be discontinued soon. The products from the Integrated Multi-satellite Retrievals for Global Precipitation Measurement (IMERG) and The Global Satellite Mapping of Precipitation (GSMaP) are analyzed as potential replacements for TMPA products. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
106
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 45 publications
8
106
0
1
Order By: Relevance
“…Regarding CSI, ETS, POD, FAR and BIAS, IMERG-F and 3B42V7 demonstrate similar behavior with better performance for IMERG-F [29]. Rozante et al [29] inferred that the different precipitation characteristics from these three products might partially result from the quality of the CPC and GPCC global precipitation data sets. In Brazil, the mean gauge number of the CPC data used to calibrate GSMaP is approximately 1000, whereas only approximately 300 rain gauges are included in the GPCC data set for bias-correcting the IMERG and TMPA products [29].…”
Section: Evaluation Of Spps Against Ground Rainfall Observationsmentioning
confidence: 96%
See 3 more Smart Citations
“…Regarding CSI, ETS, POD, FAR and BIAS, IMERG-F and 3B42V7 demonstrate similar behavior with better performance for IMERG-F [29]. Rozante et al [29] inferred that the different precipitation characteristics from these three products might partially result from the quality of the CPC and GPCC global precipitation data sets. In Brazil, the mean gauge number of the CPC data used to calibrate GSMaP is approximately 1000, whereas only approximately 300 rain gauges are included in the GPCC data set for bias-correcting the IMERG and TMPA products [29].…”
Section: Evaluation Of Spps Against Ground Rainfall Observationsmentioning
confidence: 96%
“…As parallel SPPs in the GPM-era, IMERG and GSMaP products in several regions of the world were evaluated and quantitatively compared [29,72,74,[78][79][80]. Ning et al [78] concluded that GSMaP-GAUGE version 06 (V06) performs better and has more stable quality results than IMERG-F version 04 (V04) on daily and monthly scales in Mainland China in terms of mean error (ME), RMSE, CC, and POD.…”
Section: Evaluation Of Spps Against Ground Rainfall Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth mentioning that PERSIANN estimates the precipitation based on infrared brightness temperature image (as input) and artificial neural network (as a model) (Ashouri et al 2015), while CMORPH is mainly based on microwave data and only uses infrared data for transporting the microwavebased precipitation features within periods that microwave data are not available at a location (Joyce et al 2004). Because of these improvements, IMERG precipitation products (IPPs) appeared to be better than TMPA and other SPPs in many regions, for example, India (Prakash et al 2018), Pakistan (Anjum et al 2018), Brazil (Rozante et al 2018), and East Asia (Lee et al 2019).…”
Section: Introductionmentioning
confidence: 99%